Antiviral activity of chrysin and naringenin against porcine epidemic diarrhea virus infection - Gong, Mengfei; Xia, Xuemei; Chen, Dishi; Ren, Yupeng; Liu, Yutong; Xiang, Hua; Li, Xiaohuan; Zhi, Yupeng; Mo, Yu (Frontiers in Veterinary Science, 2023)
Porcine epidemic diarrhea virus (PEDV) is one of the critical pathogens causing diarrhea in piglets and has caused huge economic losses to the swine industry in worldwide. However, there is currently no effective therapeutic medication available for the treatment of PEDV. Natural compounds are a hot topic for researching and screening antiviral lead compounds due to their abundant sources, varied activities, and low toxicity. In this study, a total of 6 compounds from different plant sources were selected for in vitro anti-PEDV screening, including Chrysin, Naringenin, Soy isoflavone, Glycyrrhetinic acid, Oleanolic acid, and Geniposide. Then two active compounds, chrysin and naringenin, were further evaluated on PEDV infected cells at different stage. And the anti-PEDV mechanism was analyzed by molecule docking and molecular dynamics. The results showed that both chrysin and naringenin showed the most significant anti-PEDV activity by increasing the cell viability and decreasing the virus copy number. Both natural compounds could inhibit viral titer, mRNA and protein levels in the prophylactic and post-viral entry stages of PEDV infection.Furthermore, chrysin and naringenin mainly interacted with viral replicase proteins such as 3CLpro and PLP-2 through hydrogen bonds and hydrophobic forces. The complexes formed by chrysin and naringenin with the two PEDV replication proteases had high stability. These results suggested that chrysin and naringenin may exert antiviral effects by interacting with the virus 3CLpro protein or PLP2 protein, thereby affecting their role in the formation of PEDV non-structural proteins or interfering with virus replication. This study lays the foundation for developing chrysin and naringenin as novel anti-PEDV therapeutic drugs.